Pengaruh Perendaman Terhadap Durabilitas Campuran AC-Base Menggunakan Batu Sungai Batupapan Kecamatan Telluwanua - Alfindo Liling; Alpius; Ika Apriyani (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This test aims to determine the durability value of the crushed stone material obtained from the Batupapan River, Telluwanua. Marshall's soaking method is used to determine the durability of this Laston AC-Base mixture. The duration of soaking used is 30 minutes to 48 hours with a stability value of 2455.26 kg – 2136.08 kg, a flow value of 3.30 mm – 4.60 mm, and for a durability value at a duration of 30 minutes to 36 hours is still below the maximum value of durability (below 90%) while 48-hour soaking does not meet (above 90%).